Retrieval and Encoding Interference: Cross-Linguistic Evidence from Anaphor Processing - Laurinavichyute, Anna; Jäger, Lena A.; Akinina, Yulia; Roß, Jennifer; Dragoy, Olga (Frontiers in Psychology, 2017)
The main goal of this paper was to disentangle encoding and retrieval interference effects in anaphor processing and thus to evaluate the hy- pothesis predicting that structurally inaccessible nouns (distractors) are not considered to be potential anaphor antecedents during language pro- cessing (Nicol & Swinney, 1989). Three self-paced reading experiments were conducted: one in German, comparing gender-unmarked reflexives and gender-marked pronouns, and two in Russian, comparing gender- marked and gender-unmarked reflexives. In the German experiment, no interference effects were found. In the first experiment in Russian, an unexpected reading times pattern emerged: in the condition where the distractor matched the gender of the reflexive’s antecedent, reading of the gender-unmarked, but not the gender-marked reflexives was slowed down. The same reading times pattern was replicated in a second experiment in Russian where the order of the reflexive and the main verb was inverted. We conclude that the results of the two experiments in Russian are in- consistent with the retrieval interference account, but can be explained by encoding interference and additional semantic processing efforts asso- ciated with the processing of gender-marked reflexives. In sum, we found no evidence that would allow us to reject the syntax as an early filer ac- count (Nicol & Swinney, 1989)